Remembering my teacher Shah Abdul Hannan - Hasan, Md. Mahmudul (2021)
In Bangladesh, people are usually attracted to the power, pomp and outward glory of public servants. It is often their stature in society that sparks interest among university graduates in choosing Civil Service as their career. None of the various perks conventionally associated with bureaucrats was salient in Shah Abdul Hannan. What attracted me to him was the depth of his knowledge, intellectual rigour and uprightness. Before meeting him, I had actually aspired to be a civil servant. It is an irony that a bureaucrat further ignited my urge for knowledge and motivated me to become an academic, and thus helped change the course of my life.